Pelvic muscle size and myosteatosis: Relationship with age, gender, and obesity - Pacicco, Thomas; Ratner, Shayna; Xi, Yin; Yokoo, Takeshi; Fetzer, David; Oz, Orhan K; Rubin, Craig D; Chhabra, Avneesh (Indian Journal of Radiology and Imaging, 2019)
Purpose: To evaluate interreader performance in the measurement of the cross-sectional area and myosteatosis of pelvic skeletal muscles using fat quantification magnetic resonance imaging (MRI) and correlate with patient anthropomorphic characteristics. Materials and Methods: A Health Insurance Portability and Accountability Act–compliant retrospective cross-sectional study was performed. Between January and April 2016, 61 patients (26 males and 35 females) underwent a lumbosacral plexus 3T MRI with a modified three-dimensional spoiled gradient echo sequence dedicated to fat quantification (mDixon Quant; Philips Healthcare). Two independent reviewers outlined muscle cross-sectional area on axial images using a freehand region of interest tool and documented proton-density fat fraction (FF) and muscle area (cm2) of the psoas, gluteus medius, gluteus maximus, and rectus femoris muscles on each side. Interreader agreement was assessed by intraclass correlation coefficient (ICC), and correlation between the measurements and subject’s age, gender, and body mass index (BMI) was assessed using multiple linear regression analysis. Results: Excellent interreader agreement was obtained (ICC ≥0.74) for all muscle groups except for the left gluteus medius area and right psoas FF which showed good agreement (0.65 and 0.61, respectively). Statistically significant (P ≤ 0.05) positive correlation was seen between the gluteal muscle FF and area with BMI, and rectus muscle FF with age and BMI. Statistically significant negative correlation between the rectus femoris area and age was also observed. Conclusion: Fat quantification MRI is a highly reproducible imaging technique for the assessment of myosteatosis and muscle size. Intramuscular FF and cross-sectional area were correlated with age and BMI across multiple muscle groups.
Keywords: Adults; fat; measurement; MRI; muscular